Manamit a gastro-generative heritage food hub in Bacolod City - Ong, Alexi Sabine U. (College of Architecture, University of the Philippines Diliman, 2025)
Food is an integral part of human life. Transcending mere sustenance, it holds profound cultural significance by preserving traditions and heritage through generations. Beyond its cultural role, it also serves as a crucial determinant of health, emphasizing the importance of fresh, locally sourced, and in-season ingredients - a practice inherently aligned with sustainability principles. However, a notable gap exists in the current literature, specifically in studies exploring the intersectionality of cultural preservation, health promotion, and sustainability within the context of food hubs. This deficiency is particularly pronounced when considering distinct culinary identities, such as that found in Bacolod City. To address this gap, the study adopts a multidisciplinary approach, drawing insights from architectural strategies, community engagement models, and global case studies of food hubs. Its main goal is to propose a dynamic food hub design that not only showcases Bacolodnon heritage food but also integrates health-centric layouts and sustainable practices, serving as a comprehensive blueprint for fostering resilient, nourished, and culturally vibrant communities. In presenting a holistic approach to food hub design, this study provides valuable insights for local government planners and communities seeking to enhance the cultural, health, and sustainability dimensions of their local food systems. These findings contribute to the ongoing dialogue surrounding the intricate balance required to create thriving, culturally rich, and sustainable food hubs tailored to unique culinary identities like Bacolod City.